Peningkatan Kekuatan Otot Tungkai Melalui Penerapan Latihan TRX di Kombinasikan dengan Metode TCSSM pada Atlet Pencak Silat - Pipit Amalia; Mulyana; Nur Ajid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study was to develop an efficient training model to improve kicking power in pencak silat athletes. The study implemented the TCSSM method to enhance lower-limb muscle strength over 16 training sessions. This method involved strength training with time-controlled sets, using 60%–80% of 1RM, 4–5 sets with repetitions based on maximum capacity calculations, and 45–60 seconds of rest between sets. Prior to the training program, a 1RM Leg Press test was conducted to assess the athletes’ physical readiness and performance capacity. The results showed an increase in the average lower-limb muscle strength measured through the 1RM leg-press test, from a pre-test mean of 56.44 kg to a post-test mean of 81.72 kg, with an improvement of +25 kg or 44%. These findings indicate that the training intervention was effective in increasing maximal lower-limb muscle strength, with a significant upward trend observed throughout the study. The study further demonstrated that the combination of TRX training and the TCSSM method significantly improved the lower-limb muscle strength of pencak silat athletes by 44%. Post-training results suggest neuromuscular adaptation and muscle hypertrophy that positively contributed to the athletes’ explosive power performance. Keywords: Lower-Limb Muscle Strength, TCSSM, TRX